Analisis Perbandingan Lesson Plan Physical Education pada Student Class 7 Junior High School Univercity Immaculate Conception (UIC) Davao city Philipine dengan RPP PJOK kelas 7 SMPN 1 Banjarbaru - Putra, Hadad Wiqoldi; Rahmadi, Rahmadi; Rakhman, Arie (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
The purpose of this study was to determine the comparative analysis of the Physical Education lesson plan at the 7th grade Junior High School Univercity Immaculate Conception (UIC) Davao city Philipine with the 7th grade PJOK lesson plan at SMPN 1 BANJARBARU. This research method is descriptive qualitative with data collection carried out by the method of observation, interview, and documentation, then data analysis using the approach by Milles and Hubberman known as the data triangulation method. The results of this study show the differences between the Physical Education Lesson Plan and the Physical Education lesson plan at SMPN 1 Banjarbaru grade 7, namelys the content of teaching materials for different learning for JHS UIC they refer to FITT (Frequency, Intensity, Time and Type) and at SMPN 1 Banjarbaru with reference to a special sports book teacher's handbook and fitness following TKJI (Indonesian physical fitness test). The process in learning the results of the implementation of the lesson plan is that the teacher provides more basic understanding before field practice and students at JHS UIC will learn in class which is divided into 2 class meetings and 2 field practice meetings while in SMPN 1 Banjarbaru only conducts 1 meeting a week and in 1 meeting is divided into two in the classroom and then field practice. This comparison is only a reference for the comparison of the Lesson Plan Physical Education Junior High School class 7 with the lesson plan of SMPN 1 Banjarbaru. In conclusion, there is a difference between the Physical Education Lesson Plan and the PJOK RPP Keywords: lesson plan Physical Education, Philipine, RPP PJOK